2023
DOI: 10.56667/dejournal.v4i1.944
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Manipulatives in Mathematics Teaching in Inclusive Education Programs in an Elementary School

Camelia Tjandra

Abstract: The use of manipulatives in mathematics education has proven effective in increasing students' understanding of mathematical concepts and involvement in the learning process. Inclusive education aims to create classrooms that are accessible to all students, regardless of their abilities or disabilities. In this context, manipulatives can play an important role in helping students with special needs, such as those with learning disabilities or physical disabilities, to understand mathematical concepts and engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This points to the fact that conceptual knowledge founded in a direct relationship of the Mathematical process with necessary manipulatives has the essential to build appropriate hands-on experiences to apply learning to new contexts. The study found significant relevance quoting to Tjandra (2021), "The use of manipulatives in Mathematics education has proven effective in increasing learners' understanding of Mathematical concepts and involvement in the learning process. "…”
Section: Introductionmentioning
confidence: 96%
“…This points to the fact that conceptual knowledge founded in a direct relationship of the Mathematical process with necessary manipulatives has the essential to build appropriate hands-on experiences to apply learning to new contexts. The study found significant relevance quoting to Tjandra (2021), "The use of manipulatives in Mathematics education has proven effective in increasing learners' understanding of Mathematical concepts and involvement in the learning process. "…”
Section: Introductionmentioning
confidence: 96%